2008
DOI: 10.1038/ajg.2008.4
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Factors Related to Hepatitis B and C in Inflammatory Bowel Disease Patients in Spain: A Nationwide, Multicenter Study

Abstract: Prevalence of HBV and HCV infection in IBD is similar to that of the general population of reference and lower than that in previously published series. This fact, in addition to the lack of association with invasive procedures, suggests the existence of adequate preventive measures in centers attending to these patients. The low percentage of effective vaccination makes it mandatory to intensify B virus vaccination in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
110
5
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 33 publications
10
110
5
9
Order By: Relevance
“…Several studies have documented poor uptake of routine vaccinations among patients with IBD ( 14,20 ). In one study of 169 IBD patients seen at an IBD center, of 145 patients on current or previous immunosuppression, only 28% reported regular fl u shots and only 9% received the pneumococcal vaccine ( 14 ).…”
Section: Vaccinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have documented poor uptake of routine vaccinations among patients with IBD ( 14,20 ). In one study of 169 IBD patients seen at an IBD center, of 145 patients on current or previous immunosuppression, only 28% reported regular fl u shots and only 9% received the pneumococcal vaccine ( 14 ).…”
Section: Vaccinationsmentioning
confidence: 99%
“…Common reasons for low rates of vaccination included patient lack of awareness and fear of side eff ects. In another study of 2076 IBD patients in Spain, only 12% of patients were vaccinated against hepatitis B ( 20 ).…”
Section: Vaccinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies have reported HBV exposure rates in IBD patients that were similar to those of the general population. REPENTINA 1, a recent large-scale cross-sectional multicentre study of 2076 IBD patients consecutively recruited at 17 Spanish hospitals, 6 found the prevalence of HBV infection to be lower than that reported in previous studies (less than 1% hepatitis B surface antigen (HBsAg)-positive and less than 10% anti-HBc-positive). However, no differences were found between CD and UC, in contrast with other studies, where the prevalence of HBV markers was higher in CD than in UC.…”
Section: What Is the Prevalence Of Hbv And Hcv Infection In Ibd Patiementioning
confidence: 85%
“…2 Studies evaluating the prevalence of HBV infection in patients with IBD are summarised in Table 1. 2,[6][7][8][9] The weighted mean prevalence of HBsAg-positive infection in the five studies included (total population, 3121 patients) was 1%. The corresponding mean value for anti-HBcpositive infection was 8.1%.…”
Section: What Is the Prevalence Of Hbv And Hcv Infection In Ibd Patiementioning
confidence: 99%